The Security Weakness of Block Cipher Piccolo against Fault Analysis. (13th March 2014) - Song, Junghwan; Lee, Kwanhyung; Jung, Younghoon
Piccolo is a 64-bit lightweight block cipher which is able to be implemented in constrained hardware environments such as a wireless sensor network. Fault analysis is a type of side channel attack and cube attack is an algebraic attack finding sufficiently low-degree polynomials in a cipher. In this paper, we show a fault analysis on the Piccolo by using cube attack. We find 16 linear equations corresponding to a round function F by cube attack, which are used to fault analysis. Our attack has the complexity of 2 8.49 and 2 9.21 encryptions with fault injections of target bit positions into Piccolo-80 and Piccolo-128, respectively. And our attack needs 2 20.86 and 2 21.60 encryptions with random 4-bit fault injections for Piccolo-80 and Piccolo-128, respectively.